On constructing the Huffman-code-based reversible variable-length codes. - Chien-Wu Tsai
In this letter, we propose a generic and efficient algorithm that can construct both asymmetrical and symmetrical reversible variable-length codes (RVLCs). Starting from a given Huffman code, the construction is based on two developed codeword selection mechanisms, for the symmetrical case and the asymmetrical case, respectively; it is shown that the two mechanisms possess simple features and can generate efficient RVLCs easily. In addition, two new asymmetrical RVLCs are constructed and shown to be very efficient for further reducing the coding overheads in MPEG-4 when operating in the reversible decoding mode
Keywords: Huffman-code-based reversible variable-length codes; RVLC; Asymmetrical reversible variable-length codes; Codeword selection mechanism; Symmetrical reversible variable-length codes